Space-air-ground integrated vehicular network for immersive driving experience - Zhi-sheng NIU; SHEN Sherman; Qin-yu ZHANG; Yu-liang TANG (物联网学报)
In order to achieve the significant advantages of next generation intelligent transportation systems,realizing the smart control of vehicles,and satisfy the vehicular demands for on-road infotainment services,a novel space-air-ground integrated vehicular network architecture was proposed by making use of the space information in terms of service coverage,time synchronization,vehicle status sensing,etc.The project would investigate three fundamental scientific issues related to the novel network:1) space-air-ground integrated network reconfiguration under dynamic space resources constraints; 2) real-time sensing and efficient integration of multi-dimensional context information; 3) real-time,reliable and secure interaction among context information.The outcomes of this project will provide the foundations both in theory and practice for highly expected smart driving,immersive driving experience,and autonomous self-driving vehicular networks.